Gender Equality Perspective of Asghar Ali Engineer: Challenges and Opportunities for Theological Feminists - Melta Adelia Putri Kurniandi (Journal of Feminism and Gender Studies, 2024)
Gender equality in the Islamic context is in deep focus, especially through the lens of feminist theology. This article explores the views of Asghar Ali Engineer, a Muslim activist, who advocates the need to treat women as equals to men and redefine sharia law regarding gender issues. The main focus is on the challenges and opportunities facing feminist theology in Islam, with an emphasis on the concept of gender equality and its impact on Muslim women. This research adopts a qualitative approach, analyzing and exploring data from key works such as "Islamic Liberation Theology" by Latief Muhaemin and the works of Asghar Ali Engineer. Feminist theologians, including Engineer, face the challenges of reconstructing religious texts, deconstructing traditional understandings that devalue women, and resolving socio-cultural challenges related to religious law and social norms. With a socio-theological approach, they emphasize the importance of understanding the social context and reinterpreting key concepts to suit the needs of the times. In an effort to create a non-exploitative life order, theological feminists such as Engineer strive to provide equal opportunities for women and men, including in aspects of leadership, to bring positive changes in the interpretation of Islamic religious teachings in the 21st century.